2010
DOI: 10.1111/j.1574-6941.2009.00826.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alginate and inulin on intestinal microbial ecology of weanling pigs reared under different husbandry conditions

Abstract: The effects of inulin and alginate on intestinal microbial ecophysiology were investigated in piglets fed a diet (C) with 0.1% alginate (C+A) or 1.5% inulin (C+I) from weaning at day 28. The experiment was performed at an experimental farm (EF) and a commercial farm (CF). Digesta was collected from the ileum, caecum and colon of four piglets from each group on days 29, 30, 33 and 39. The metabolite concentrations changed with age. Colonic and caecal metabolites were affected by prebiotic treatment. Changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
34
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 47 publications
5
34
0
1
Order By: Relevance
“…The results from our study showed that the b-glucan exerted a similar reducing effect on coliform counts. Janczyk et al (2010) demonstrated that dietary supplementation with alginate resulted in higher enterococci counts in the distal small intestine, caecum and proximal colon of pigs, in comparison with counts obtained from animals fed inulin or a control diet. Counts of lactobacilli decreased in all GIT segments in the experimental group after the feeding period (Janczyk et al, 2010).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…The results from our study showed that the b-glucan exerted a similar reducing effect on coliform counts. Janczyk et al (2010) demonstrated that dietary supplementation with alginate resulted in higher enterococci counts in the distal small intestine, caecum and proximal colon of pigs, in comparison with counts obtained from animals fed inulin or a control diet. Counts of lactobacilli decreased in all GIT segments in the experimental group after the feeding period (Janczyk et al, 2010).…”
Section: Discussionmentioning
confidence: 91%
“…Janczyk et al (2010) demonstrated that dietary supplementation with alginate resulted in higher enterococci counts in the distal small intestine, caecum and proximal colon of pigs, in comparison with counts obtained from animals fed inulin or a control diet. Counts of lactobacilli decreased in all GIT segments in the experimental group after the feeding period (Janczyk et al, 2010). Although alginate is a polysaccharide derived from Phaeophyta, its chemical structure, molecular and chain conformation are different from the laminarin component, thus possessing not only different biological properties but also behaving as a substrate for different LAB phylotypes.…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…Both phylogenetic microarrays (Paliy et al, 2009;Rajilic-Stojanovic et al, 2009;Kang et al, 2010) and high-throughput sequencing methods are now used more frequently to examine gut microbiome diversity, but the development of robust quantitative methods to reveal the biogeographical features of the gut microbiota is considered a 'great challenge' and 'the diversity and biogeography of the gut microbiota needs to be defined at varying scales of resolution' (Peterson et al, 2008). Although some clustering and ordination methods of numerical ecology are commonly used to compare microbial community profiles through open source software (for example, QIIME (Caporaso et al, 2010)), and increasingly used in gut microbiomics research (Fuentes et al, 2008;Biagi et al, 2010;Janczyk et al, 2010), we contend that, in addition to those methods, there are additional useful numerical ecology methods that can be used. For instance, constrained ordination methods are being increasingly used for the analysis of mammalian gene expression (Culhane et al, 2002;Baty et al, 2006Baty et al, , 2008 and of the microbial communities present in terrestrial and aquatic samples (see Ramette (2007) for a recent review).…”
Section: Introductionmentioning
confidence: 99%